Challenges and effectiveness of eclectic method at higher secondary level in rural Bangladesh (IIUC Studies, 2021)
This article addresses the challenges and effectiveness of implementing Eclectic Method in Language Teaching at higher secondary level in the rural context of Bangladesh. This paper adopts a qualitative approach, and six rural colleges are selected to conduct the research. These institutions are located in Chittagong District, Bangladesh. Ten English teachers were interviewed face-to-face to collect data about the challenges they have faced and the effectiveness they observed in applying Eclectic Approach in their colleges. The findings show the applicability of Eclectic Approach in several ways that include flexibility in teaching, variety in adapting language teaching aspects, allowing new ideas, dynamic classroom facilities, enhancing teachers’ and students’ respect for cross-culture and multi-lingual classroom. The findings indicate some hurdles in teaching English that include lack of trained teachers, improper text books, teachers’ insufficient knowledge, rigid mentality of the rural teachers, insufficient infrastructural facilities, and taking pride in mother-language etc. This research may help the policy makers of language and curriculum design in developing effective strategies for Eclectic practices in rural Bangladesh.IIUC Studies Vol.17, December 2020: 73-86